Sleeping with the head [up] of the bed tilted up: physiology & therapy - Fan, Chie Wei (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
Orthostatic hypotension (OH) is common and affects people with increasing age and co-morbidity. It is associated with increased vascular risk, falls and dementia. While pharmacological and non-pharmacological treatments exist they are either poorly tolerated or poorly studied. One of the non-pharmacological therapies is sleeping with the head of the bed elevated (SHU). This treatment option has been described since the 1940’s. However, the scientific evidence for SHU, up to now, has been case reports in middle aged people (i.e. younger than 65 years) and SHU has been prescribed in conjunction with anti-hypotensive medications and extra salt intake so that direct benefits are unclear. . It is also unclear to what extent it is used in people aged 65 and over, the group with the greatest prevalence of OH. Furthermore, there is a lack of clarity in the expert guidelines to what height the head of the bed should be tilted even though this factor is likely to be important for physiological effect. Where specific heights are given, for instance 18 inches, this height is unlikely to be tolerated by older people.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin